Gaya Kepemimpinan Paternalistik Kepala Sekolah dan Ilim Organisasi terhadap Kepuasan Kerja Guru SDIT Ar-Rohmaniyah Kec. Tanah Sareal Kota Bogor - Muhamad Robie Awaludin S; Sekar Pratiwi (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2021)
The purpose of this study was to determine and describe the influence of paternalistic leadership style and organizational climate on teacher job satisfaction at SDIT AR-Rohmaniyah, Tanah Sareal District, Bogor City. The research method used in this research is a quantitative method using correlational techniques and analyzed using multiple regression techniques. The test results found that the paternalistic leadership style had an effect on but not significant on teacher job satisfaction, organizational climate had a positive and significant effect on teacher job satisfaction and there was a positive and significant influence between paternalistic leadership style and organizational climate together on teacher job satisfaction. Keywords: Paternalistic Leadership Style. Organizational Climate, Teacher Job Satisfaction.